Birth season and gross brain morphology associated with early neurodevelopment in schizophrenia spectrum patients and healthy subjects - Takahashi, Tsutomu; Sasabayashi, Daiki; Takayanagi, Yoichiro; Kobayashi, Haruko; Torigoe, Misako; Sakamoto, Kazumi; Yuasa, Yusuke; Tsujii, Noa; Noguchi, Kyo; Suzuki, Michio (Psychiatry research. Neuroimaging, 2023)
•This MRI study investigated the effects of birth seasons on gross brain morphology.•Schizophrenia, schizotypal disorder, and healthy control groups were examined.•Summer births were related to well-developed insular gyri independent of diagnosis.•Birth seasons did not affect the pathophysiology of schizophrenia spectrum. This MRI study examined the effects of birth seasons on gross brain characteristics, such as the prevalence/size of midline brain structures (cavum septi pellucidi and adhesio interthalamica), orbitofrontal surface morphology, and insular gross anatomy, in 135 patients with schizophrenia, 47 with schizotypal disorder, and 88 healthy controls. Birth seasons only affected the insular anatomy. Summer-born subjects (N = 110) were characterized by more developed left insular gyri than winter-born subjects; however, this effect had no diagnostic specificity. The present results do not support birth seasons affecting the neurodevelopmental pathology of schizophrenia spectrum.